Construction and testing of the simulation polygon for the protection of critical information resources - Корнієнко, Б. Я.; Галата, Л.П. (Science-based technologies, 2017)
In this article, the process of constructing an imitation polygon as a method for studying the behavior of the system of protection of critical information resources is considered. The graphical network simulator application is used to construct the simulation polygon. The functionality of the GNS3 package is explored. The main properties of the simulation ground of protection of critical information resources are considered. The testing of a built-up simulation ground for protecting critical information resources by software was performed and network port scan was performed using the Zenmap utility. Information on the internal network and internal interface of Cisco ASA are gathered. Using the hping3 utility, a stress test of the network is implemented - the Syn-Flood attack on the server's failure. The counteraction of this attack with the use of TCP SYN Cookies is implemented.